Before the fall - Hawley, Noah (New York : Grand Central Publishing, 2016)
On a foggy summer night, eleven people--ten privileged, one down-on-his-luck painter--depart Martha's Vineyard headed for New York. Sixteen minutes later, the unthinkable happens: the passengers disappear into the ocean. The only survivors are Scott Burroughs--the painter --and a four-year-old boy, who is now the last remaining member of a wealthy and powerful media mogul's family. With chapters weaving between the aftermath of the tragedy and the backstories of the passengers and crew members-- including a Wall Street titan and his wife, a Texan-born party boy just in from London, a young woman questioning her path in life, and a career pilot--the mystery surrounding the crash heightens. As the passengers' intrigues unravel, odd coincidences point to a conspiracy: Was it merely dumb chance that so many influential people perished? Or was something far more sinister at work?
Keywords: Aircraft accident victims -- Fiction; Airplane crash survival -- Fiction; Large type books; Martha's Vineyard (Mass.) -- Fiction; Thrillers (Fiction)